(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
End of life bioethics includes a wide range of issues, all of them dealing with the value of human life, on human dignity, on the idea of justice and good. In the field of medical sciences, the recent technological progress has deeply changed traditional concepts such as life, death, vegetative state and imposes a rethinking and a distinction between biological and biographic life. The paper aims at comparing the doctrine of the Roman catholic church with and Protestant theology, which is more adherent to a secular ethics with regards to the safeguard of human dignity. The goal of this analysis is to underline the complex dilemmas that a modern and pluralistic society is called to deal with in a context of mutual respect and tolerance.